Tracing local sources and long-range transport of PM10 in central Taiwan by using chemical characteristics and Pb isotope ratios - Po-Chao Wu (Nature Portfolio, 2021)
Abstract Central Taiwan is among the most heavily polluted regions in Taiwan because of a complex mixing of local emissions from intense anthropogenic activities with natural dust. Long-range transport (LRT) of pollutants from outside Taiwan also contributes critically to the deterioration of air quality, especially during the northeast monsoon season. To identify the sources of particulate matter < 10 μm (PM10) in central Taiwan, this study performed several sampling campaigns, including three local events, one LRT event, and one dust storm event, during the northeast monsoon season of 2018/2019. The PM10 samples were analyzed for water-soluble ion and trace metal concentrations as well as Pb isotope ratios. Local sediments were also collected and analyzed to constrain chemical/isotopic signatures of natural sources. The Pb isotope data were interpreted together with the enrichment factors and elemental ratios of trace metals in PM10, and reanalysis data sets were used to delineate the sources of PM10 in central Taiwan. Our results suggested that Pb in PM10 was predominantly contributed by oil combustion and oil refineries during the local events (48–88%), whereas the lowest contributions were from coal combustion (< 21%). During periods of high wind speed, the contribution from natural sources increased significantly from 13 to 31%. Despite Pb represented only a small portion of PM10, a strong correlation (r = 0.89, p  < 0.001, multiple regression analysis) between PM10 mass and the concentrations of Pb, V, and Al was observed in the study area, suggesting that the sources of PM10 in central Taiwan can be possibly tracked by using chemical characteristics and Pb isotopes in PM10. Moreover, the Pb isotopic signals of PM10 collected during the LRT event confirmed the impact of LRT from Mainland China, and the chemical characteristics of the PM10 significantly differed from those of the PM10 collected during local events. This study demonstrates the robustness of using a combination of Pb isotopic compositions and chemical characteristics in PM10 for source tracing in complex and heavily polluted areas.